Herbal Industry Wastes as Potential Materials for Biofuel Production - Aneta Sienkiewicz; Alicja Piotrowska-Niczyporuk; Andrzej Bajguz (Proceedings, 2020)
Due to the increasing awareness of the depletion of fossil fuel resources and environmental issues, biodiesel as alternative fuel has become more and more attractive in the recent years. In this research, the characterization of herbal industry wastes as a potential feedstock for biodiesel production was carried out. There results of analytical identification of the fatty acid methyl esters (FAME) obtained in the transesterification reaction are presented. The reaction conditions were optimized, considering hexane ratio and catalyst concentration (methanol and KOH) for both steps. The FAME were extracted from the herbal samples by ultrasound-assisted extraction and subsequently were identified by gas chromatography-mass spectrometry (GC-MS) using single ion monitoring (SIM) method. Additionally, the selected properties of some bioesters were analyzed. This study determined the compounds which are ideal for fuel production. The unsaturated fatty acids were found in higher amounts than saturated fatty acids. Linoleic acid (C18:2n6c) was the major unsaturated fatty acid in herbal wastes, while palmitic acid (16:0) was the major saturated fatty acid. The application of the optimized method also revealed differences in the physical and chemical properties of isolated FAME mixtures compared to conventional diesel fuel. In this research work, for the first time, the possibilities of using the herbal industry wastes as a potential feedstock for biodiesel production are assessed.